Another turn of the screw on Dennett and artifactual hermeneutics: tensions and aporias - Lawler, Diego; Parente, Diego (Estudios de Filosofía, 2013)
This work focuses on the application to technical artefact of the philosophical approach proposed by Daniel Dennett to elucidate the field of artificial things. In particular, it suggests two things. Firstly, that this application does not allow us to fully understand the normative dimension that covers the practical sphere of our production and use of technical artefact. Secondly, that this application promotes a very liberal approach on attribution of functions to technical artefact that makes unrecognisable the very idea of technical function. This paper is composed of three sections. The first one characterizes the artifactual hermeneutics promoted by Dennett’s approach. It analyses the stance of reverse engineering, the physical one and the design and intentional stance respectively. The second part discusses the analogy between texts and artefact and reconstructs the strategy embedded in this analogy. The last part presents a critical assessment of Dennett’s proposal regarding its application to the field of technical artefact.